PPARγ as a Novel Therapeutic Target in Lung Cancer - Aravind T. Reddy; Sowmya P. Lakshmi; Raju C. Reddy (PPAR Research)
Lung cancer is the leading cause of cancer-related death, with more than half the patients having advanced-stage disease at the time of initial diagnosis and thus facing a poor prognosis. This dire situation poses a need for new approaches in prevention and treatment. Peroxisome proliferator-activated receptor γ (PPARγ) is a ligand-activated transcription factor belonging to the nuclear hormone receptor superfamily. Its involvement in adipocyte differentiation and glucose and lipid homeostasis is well-recognized, but accumulating evidence now suggests that PPARγ may also function as a tumor suppressor, inhibiting development of primary tumors and metastases in lung cancer and other malignancies. Besides having prodifferentiation, antiproliferative, and proapoptotic effects, PPARγ agonists have been shown to prevent cancer cells from acquiring the migratory and invasive capabilities essential for successful metastasis. Angiogenesis and secretion of certain matrix metalloproteinases and extracellular matrix proteins within the tumor microenvironment are also regulated by PPARγ. This review of the current literature highlights the potential of PPARγ agonists as novel therapeutic modalities in lung cancer, either as monotherapy or in combination with standard cytotoxic chemotherapy.